Resonant inelastic x-ray scattering investigation of the crystal-field splitting of Sm3+in SmB6 - Amorese, Andrea; Haverkort, Maurits W. (Physical review, 2019)
The crystal-field (CF) splitting of the 6H5/2 Hund's rule ground state of Sm3+ in the strongly correlated topological insulator SmB6 has been determined with high-resolution resonant inelastic x-ray scattering (RIXS) at the Sm M5 edge. The valence selectivity of RIXS allows isolating the crystal-field-split excited multiplets of the Sm3+ (4f5) configuration from those of Sm2+ (4f6) in intermediate valent SmB6. We find that the quartet Γ8 ground state and the doublet Γ7 excited state are split by ΔCF6H5/2=20±10 meV which sets an upper limit for the 4f bandwidth. This indicates an extremely large mass renormalization from the band-structure value, pointing out the need to consider the coefficients of fractional parentage for the hopping of the 4f electrons. The tiny bandwidth explains the small value of the indirect gap and puts constraints on the energies of the topological surface states.